Prevalence of Gestational Diabetes and its Related Risk Factors among Rural Pregnant Women - Veerappan, Pragadeesh Raja; Lenin, Dharani; Sahaya Sona Thresa (Indonesian Socety of Obstetrics and Gynecology, 2024)
Abstract Objectives: To estimate the prevalence of gestational diabetes among rural pregnant women and to assess the related risk factors among gestational diabetes mothers in rural areas. Methods: A community-based cross-sectional study was conducted among antenatal mothers between 24 to 28 weeks of gestation in rural areas of Kancheepuram district, Tamil Nadu, for a period of one year from January 2017 to December 2017. Data were collected using a semi-structured questionnaire through face-to-face interviews with antenatal mothers regarding their demographic profile, obstetric history, nutrition, and lifestyle. The level of stress was assessed using the Perceived Stress Scale. Oral glucose tolerance tests (OGTT) were performed after an overnight fast of at least 12 hours, with a 75 g glucose load administered, and venous samples were drawn after 2 hours. GDM was diagnosed using specific criteria. Results: Out of 244 antenatal mothers, 36 (14.8%) were found to have gestational diabetes. The majority of gestational diabetes mothers were housewives (p=0.02). In the current study, most of the GDM mothers were from lower-middle-class families (p=0.04). GDM mothers with a family history of chronic diseases like diabetes, hypertension, and heart disease (p=0.009), as well as those with an increased number of pregnancies, had a higher risk of gestational diabetes (47.6%), which was statistically significant (p=0.001). Patients with hypertension and thyroid disorders were also at an increased risk of developing diabetes during pregnancy (p=0.04). Past history of surgery (p=0.03), low calorie intake, and nutritional deficiencies in their diet (p=0.02) were other identified risk factors. Conclusion: This study suggests that the prevalence of gestational diabetes is high among rural antenatal mothers. Therefore, these risk factors should be identified and managed through a risk-based approach to minimize the complications of GDM in both the mother and fetus. Keywords: diabetes, pregnancy, stress.